Informal Patient Payments and Bought and Brought Goods in the Western Balkans - A Scoping Review - Sofie Buch Mejsner; Leena Eklund Karlsson (Kerman University of Medical Sciences, 2017)
Introduction Informal patient payments for healthcare are common in the Western Balkans, negatively affecting public health and healthcare. Aim To identify literature from the Western Balkans on what is known about informal patient payments and bought and brought goods, to examine their effects on healthcare and to determine what actions can be taken to tackle these payments. Methods After conducting a scoping review that involved searching websites and databases and filtering with eligibility criteria and quality assessment tools, 24 relevant studies were revealed. The data were synthesized using a narrative approach that identified key concepts, types of evidence, and research gaps. Results The number of studies of informal patient payments increased between 2002 and 2015, but evidence regarding the issues of concern is scattered across various countries. Research has reported incidents of informal patient payments on a wide scale and has described various patterns and characteristics of these payments. Although these payments have typically been small - particularly to providers in common areas of specialized medicine - evidence regarding bought and brought goods remains limited, indicating that such practices are likely even more common, of greater magnitude and perhaps more problematic than informal patient payments. Only scant research has examined the measures that are used to tackle informal patient payments. The evidence indicates that legalizing informal patient payments, introducing performance-based payment systems, strengthening reporting, changing mentalities and involving the media and the European Union (EU) or religious organizations in anti-corruption campaigns are understood as some of the possible remedies that might help reduce informal patient payments. Conclusion Despite comprehensive evidence regarding informal patient payments, data remain scattered and contradictory, implying that informal patient payments are a complex phenomenon. Additionally, the data on bought and brought goods illustrate that not much is known about this matter. Although informal patient payments have been studied and described in several settings, there is still little research on the effectiveness of such strategies in the Western Balkans context.